The Effect of Financial Distress and Accounting Prudence on Earnings Management in Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Putra, Alvin Andika; Fitrini Mansur; Misni Erwati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of financial distress and accounting prudence on earnings management. The population in this study were transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The research sample was 22 companies taken with purposive sampling technique. This research is a quantitative study using secondary data. The data analysis technique used is multiple linear regression analysis. The results showed that financial distress has no effect on earnings management, while accounting prudence has a significant effect on earnings management. In addition, the results showed that financial distress and accounting prudence simultaneously have a significant effect on earnings management